Application of Scanning Kelvin Probe in the Study of Protective Paints - Nazarov, Andrej; Thierry, Dominique (Frontiers in Materials, 2019)
Industrial coatings are composed of layers of different polymers (top coats, primers) containing pigments, corrosion inhibitors, and fillers as well as additives. For corrosion protection, it is vitally important to preserve the strong adhesion and long-term stability of the metal-polymer interface in corrosive environments. In recent decades, the performance of painted materials increased, which requires the application of advanced methods for quick assessing, ranking and predicting corrosion stability. Scanning Kelvin probe (SKP) is a highly sensitive and non-invasive technique to analyze in situ the metal-polymer interface of high-performance industrial coatings. SKP is able to monitor the adhesion and corrosion underneath different kinds of paints without the need for long-term corrosion tests. SKP is a localized electrochemical technique with a spatial resolution in the range of 70-100 µm. Hence, it is possible to obtain information about the intact and corroding portions of the interface at defect sites, corrosion blisters, contaminants and intermetallics, quality of pretreatments, and the development of galvanic couples that lead to corrosion de-adhesion of the polymeric coatings. This article reviews the application of SKP to the determination of the mechanisms of corrosion de-adhesion of model paints, thick marine paints, coatings with zinc rich primers, automotive paints and coil coatings applied on galvanized steel substrates.